Simulation and Analysis of Wind-Solar Hybrid Energy Conversion System - Harshkumar Subhashbhai Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Solar and wind are the most prevalent resources due to their accessibility and the simplicity of their conversion into power. Each renewable resource necessitates a DC/DC boost converter with MPPT management for power generation. The maximum power point tracking (MPPT) technology is utilized to achieve optimal efficiency in photovoltaic (PV) and wind energy systems. Perturbation and Observation-MPPT approach is employed in photovoltaic systems where direct current voltage serves as the perturbation variable. In wind energy systems, a perturbation variable in the form of direct current is utilized in the modified perturb and observe maximum power point tracking algorithm. The modified perturb and observe technique exhibits stability and rapid tracking in response to abrupt changes in wind speed. The greatest Power Point Tracking (MPPT) technique employed with a boost converter optimally takes the greatest power from the available source. The simulation of both renewable energy sources is conducted independently in PSIM 9.0 utilizing various MPPT approaches.
Keywords: Solar PV; wind energy system; MPPT; hybrid power system; simulation; RES